Anti-dazzle anti-reflection plate

By setting an anti-glare layer on the anti-reflection plate and using a curable composition of specific particles to make the anti-glare layer, the problems of uneven anti-glare properties and low production efficiency in the prior art are solved, and high anti-reflection and excellent Anti-glare properties are suitable for a variety of display devices.

CN119493199APending Publication Date: 2025-02-21FUKUBI KAGAKU IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411096522.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2024-08-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art has problems such as uneven anti-glare properties, limitations due to the type and size of substrates, high production efficiency and cost in preventing reflection and glare of display devices.

Method used

The anti-glare layer is provided on the surface of the anti-reflection plate and the anti-glare layer is produced using a curable composition coating method containing inorganic particles of a specific particle size, so as to control the linear roughness characteristics of the surface, thereby achieving excellent anti-glare sex.

Benefits of technology

It achieves high anti-reflectiveness and excellent anti-glare properties, is suitable for a variety of display devices, including automotive instrument panels and outdoor smartphones and tablets, and has advantages in terms of productivity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004988090700000221
    Figure BDA0004988090700000221
  • Figure BDA0004988090700000251
    Figure BDA0004988090700000251
  • Figure BDA0004988090700000271
    Figure BDA0004988090700000271
Patent Text Reader

Abstract

The present invention relates to an anti-glare and anti-reflection plate, and provides an anti-glare and anti-reflection plate having the following excellent anti-reflection and anti-glare properties: the plate is an anti-glare and anti-reflection plate comprising a hard coating layer, an anti-glare layer, and an anti-reflection film, in which the hard coating layer, the anti-glare layer, and the anti-reflection film are laminated in this order on a transparent resin substrate, the anti-glare layer is made of a cured product of a composition containing 0.1-15.0 parts by mass of inorganic particles having an average particle diameter (D50) of 500-700 nm with respect to 100 parts by mass of a polymerizable acrylate compound, and the line roughness characteristics on the surface of the anti-glare and anti-reflection plate as defined in JIS B 0601 are as follows. The arithmetic average roughness (Ra) is 0.03 [mu] m or more and 0.20 [mu] m or less, the average length (RSm) is 10 [mu] m or more and 70 [mu] m or less, the skewness (Rsk) is-0.05 or more and 1.50 or less, the kurtosis (Rku) is 2.0 or more and 5.0 or less, and the maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less. The haze value of the anti-dazzle and anti-reflection plate is 0.5% to 20.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-glare anti-reflection sheet having excellent anti-reflection properties and anti-glare properties. Background Art

[0002] In the prior art, in various display devices such as personal computers, mobile phones, LCD monitors, ATMs, automobile instrument panels, and navigation panels, preventing reflection and glare to maintain visibility under natural light and artificial light has always been considered a problem, and various countermeasures have been implemented to solve the problem.

[0003] As a countermeasure, an anti-reflection film (sheet) has been developed, and the purpose is achieved by attaching the film to the surface of the display device. The anti-reflection film includes an anti-reflection film composed of an interference layer in its surface layer part, which reduces the reflectivity on the surface, prevents reflected glare, etc., and ensures good visibility.

[0004] Another optical property that affects visibility is glare caused by diffuse reflection and diffusion of light on a surface. In order to suppress glare (hereinafter also referred to as anti-glare property), a technique of imparting concavity and convexity to a surface for the purpose of scattering and diffusing light has been developed.

[0005] In the prior art, as a method for imparting concavity and convexity to the surface, a method such as embossing with a mold subjected to concavity and convexity processing using hot pressing or concavity and convexity imparting using an embossing roller is adopted (see JP 2018-77279A and JP 2004-333936A). However, such physical imparting methods have the following problems:

[0006] - Variation in anti-glare properties, because embossing cannot be performed uniformly.

[0007] - Anti-glare properties vary depending on the kind of substrate.

[0008] - The embossing range is limited due to the size of the embossing machine and the size of the substrate.

[0009] - The anti-glare properties differ between the center and the ends of the substrate, so the ends must be cut off, which reduces the usable effective area and reduces productivity.

[0010] -Added process steps and batch processing lead to poor production efficiency and increased costs. Summary of the invention

[0011] As a result of intensive studies to solve the above-mentioned problems, the inventors of the present application have found that the linear roughness characteristics of the surface can be controlled and anti-glare properties can be achieved by providing an anti-glare layer on the surface layer portion of an anti-reflection plate and manufacturing the anti-glare layer by using a coating method in which a curable composition containing particles of a specific particle size is coated on the layer and cured, and have completed the present invention.

[0012] That is, according to the present invention, an anti-glare anti-reflection plate is provided, which includes a hard coating layer, an anti-glare layer and an anti-reflection film stacked in sequence on a transparent resin substrate, the anti-glare layer is made of a cured product of a composition, the composition contains 0.1 to 15.0 parts by mass of inorganic particles having an average particle size (D50) of 500 nm to 700 nm relative to 100 parts by mass of a polymerizable acrylate compound, and the line roughness characteristics defined in JIS B0601 on the surface of the anti-glare anti-reflection plate are as follows: the arithmetic mean roughness (Ra) is greater than 0.03 μm and less than 0.20 μm, the average length (RSm) is greater than 10 μm and less than 70 μm, the skewness (Rsk) is greater than -0.05 and less than 1.50, the kurtosis (Rku) is greater than 2.0 and less than 5.0, and the maximum peak height (Rp) / maximum valley depth (Rv) is greater than 1.0 and less than 3.0.

[0013] In the invention of the antiglare antireflection sheet, it is preferred that:

[0014] 1) The antireflection film is composed of a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 nm to 200 nm, the inorganic particles are silica particles, and the haze value of the antiglare antireflection plate is 0.5% to 20.0%,

[0015] 2) The anti-reflection film includes, in order, a medium refractive index layer having a refractive index of 1.50 to 1.75 and a layer thickness of 50 nm to 200 nm, a high refractive index layer having a refractive index of 1.60 to 2.00 and a layer thickness of 50 nm to 200 nm, and a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 nm to 200 nm, the refractive index of the high refractive index layer being higher than that of the medium refractive index layer, the inorganic particles being silica particles, and the haze value of the anti-glare anti-reflection plate being 0.5% to 15.0%,

[0016] 3) the antiglare layer is made of a cured product having a composition, the composition comprising 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 parts by mass of a metal chelate compound, and 0.0 to 45.0 parts by mass of silica fine particles, relative to 100 parts by mass of a polymerizable acrylate compound comprising 70 to 90 parts by mass of a hexafunctional urethane (meth)acrylate and 30 to 10 parts by mass of a difunctional to tetrafunctional (meth)acrylate compound (total 100 parts by mass),

[0017] 4) the average layer thickness of the anti-glare layer is 100 nm to 500 nm, and

[0018] 5) A protective layer and an antifouling layer are further laminated in this order above the antireflection film (on the viewing side).

[0019] The anti-glare anti-reflection plate of the present invention has excellent anti-glare properties in addition to high anti-reflection properties. Therefore, the anti-glare anti-reflection plate is not only effectively used for general display devices, but also for panels of devices requiring high visibility, such as automobile instrument panels and touch panels of automobile navigation systems. In addition, the anti-glare anti-reflection plate can also be applied to display devices used outdoors, such as smart phones and tablet computers.

[0020] Since the above antiglare antireflection sheet can be manufactured by a coating method, it has significant industrial value, such as suppressing the variation of antiglare properties, being able to manufacture any antiglare antireflection sheet without being affected by the size of the substrate, and being advantageous in terms of productivity and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a laser photograph of the surface of the antiglare antireflection plate obtained in Example 1;

[0022] Figure 2 A graph showing a measured cross-sectional curve and a roughness curve of the antiglare antireflection sheet obtained in Example 1;

[0023] Figure 3 is a laser photograph of the surface of the antiglare antireflection sheet obtained in Comparative Example 1; and

[0024] Figure 4 Graphs showing the measured cross-sectional curve and roughness curve of the antiglare antireflection sheet obtained in Comparative Example 1. DETAILED DESCRIPTION

[0025] <Anti-glare anti-reflective sheet>

[0026] The antiglare antireflection sheet of the present invention has a basic structure in which a transparent resin substrate, a hard coat layer, an antiglare layer, and an antireflection film are laminated in this order.

[0027] The anti-glare anti-reflection plate of the present invention is not limited to this structure, as long as it has the above-mentioned basic structure. For example, it is suitable to set a protective layer that imparts wear resistance on the anti-reflection film (viewing field side), and further set an anti-fouling layer on the protective layer to prevent the pollution caused by oily components or chemical solutions. In addition, an adhesive layer made of acrylic adhesive, rubber adhesive or silicone adhesive can be set on the back side of the anti-glare anti-reflection plate. In addition, hard coating, anti-glare layer and anti-reflection film can be stacked on the front and back sides of the transparent resin substrate.

[0028] The antiglare antireflection sheet has the following surface characteristics (line roughness characteristics defined in JIS B 0601) and has excellent antiglare properties.

[0029] The arithmetic mean roughness (Ra) is 0.03 μm or more and 0.20 μm or less,

[0030] The average length (RSm) is 10 μm or more and 70 μm or less,

[0031] The skewness (Rsk) is greater than -0.05 and less than 1.50,

[0032] The kurtosis (Rku) is 2.0 or more and 5.0 or less,

[0033] The maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less.

[0034] [Arithmetic mean roughness (Ra)]

[0035] The arithmetic mean roughness (Ra) represents the average value of R(x) <absolute value> in the reference length. The arithmetic mean roughness (Ra) is 0.03 μm or more and 0.20 μm or less.

[0036] [Average length (RSm)]

[0037] The average length (RSm) represents the average length of the contour curve element in the reference length, and Xsi is the length corresponding to one contour line element. In this case, the peaks (valleys) constituting the contour elements have minimum height and minimum length regulations, and any peaks (valleys) with a height (depth) of less than 10% of the maximum height or a length of less than 1% of the length of the calculation interval are regarded as noise and are considered to be part of the valleys (peaks) that are continuous in front and behind. The average length (RSm) is more than 10μm and less than 70μm, and it can be seen that not only the unevenness caused by the contained inorganic particles contributes, but also the unevenness of the curable polymerizable acrylate compound.

[0038] [Skewness(Rsk)]

[0039] The skewness (Rsk) represents the cubed average value of R(x) in the reference length (made dimensionless by the cube of the root mean square height (Rq)), and is a parameter closely related to tribology (friction).

[0040] The skewness indicates the degree of strain and shows the symmetry of the distribution of peaks and valleys. In the case of a normal distribution, the skewness is 0 (zero), and in the case of a worn surface, the skewness is negative, indicating that the distribution is biased upward. The skewness (Rsk) is greater than -0.05 and less than 1.50, indicating that there are many relatively fine peaks.

[0041] [Kurtosis (Rku)]

[0042] The kurtosis (Rku) represents the fourth-power average of R(x) in the reference length (made dimensionless by the fourth power of the root mean square height (Rq)), and is a parameter closely related to tribology (friction).

[0043] Kurtosis indicates sharpness and in the case of normal distribution is 3. When the kurtosis (Rku) is 2.0 or more and 5.0 or less, this indicates that the sharpness of the surface is not very high, but the entire surface is rough.

[0044] [Maximum peak height (Rp) / Maximum valley depth (Rv)]

[0045] This indicates how many times the height of the peak is the depth of the valley. The larger the value, the higher the peak and the shallower the valley. When the maximum peak height (Rp) / maximum valley depth (Rv) is greater than 1.0 and less than 3.0, this indicates that the height of the peak is relatively greater than the depth of the valley.

[0046] [Haze value]

[0047] The antiglare antireflection sheet of the present invention satisfies the above surface characteristics, and obtains a haze value of 0.5% to 20.0% and excellent antiglare properties. The haze value is affected by the layer structure of the antireflection film, but since the haze value falls within this range, glare is suppressed.

[0048] The haze value is a physical property value used as a measure of anti-glare properties. The higher the haze value, the higher the anti-glare properties, but when the haze value exceeds 20.0%, the transparency of the anti-glare anti-reflection sheet decreases, which is undesirable. When the haze value is less than 0.5%, the transparency is high, but the glare increases and the visibility decreases. The appropriate haze value is 0.5% to 15.0%, and the more appropriate haze value is 0.8% to 13.5%.

[0049] [Transparent resin substrate]

[0050] As the resin substrate, a light-transmitting resin substrate is appropriately used according to the purpose of use. For example, a substrate made of a thermoplastic resin having a total light transmittance of 85% or more at a wavelength of 750nm to 400nm is preferred. The thickness of the substrate is arbitrarily selected according to the purpose of use, but is generally 0.5mm to 3mm.

[0051] Examples of such light-transmitting thermoplastic resins may include acrylic resins represented by polymethyl methacrylate, polycarbonate resins, polyethylene terephthalate resins, polyallyl diglycol carbonate resins, polystyrene resins, and the like.

[0052] The substrate may be a laminated resin substrate in which two of the above resins are laminated, but preferably the surface on which the hard coat layer is formed is formed of an acrylic resin, a polycarbonate resin or a polyethylene terephthalate resin. Preferably, a laminated resin substrate made of a polycarbonate resin and an acrylic resin is used.

[0053] Furthermore, such a transparent resin substrate may be colored with an oil-soluble dye or the like as long as its light transmittance is not impaired.

[0054] [Hard coating]

[0055] A hard coat layer is laminated on the transparent resin substrate, and an antiglare layer described later is formed on the hard coat layer.

[0056] The hard coat layer is a layer that contributes to the strength of the antiglare antireflection plate and the adhesion between the transparent resin substrate and the antiglare layer. By improving the adhesion, the antiglare antireflection plate of the present invention has excellent abrasion resistance and hardness.

[0057] The thickness of the hard coating layer is generally 1 μm to 5 μm. When the thickness is less than 1 μm, the strength and other characteristics of the hard coating layer are impaired, and when the thickness exceeds 5 μm, cracks are easily generated. The thickness is preferably 1 μm to 3 μm, and particularly preferably 1 μm to 2 μm.

[0058] In order to obtain excellent adhesion between the transparent resin substrate and the anti-glare layer and excellent hardness of the hard coating layer itself, a hard coating layer made of a cured product of a curable composition containing a polymerizable acrylate compound is suitable, wherein the curable composition contains 70% to 90% by mass of a hexafunctional or higher urethane (meth) acrylate compound, silica fine particles, a silane coupling agent and a metal chelate compound.

[0059] A typical curable composition has a formulation of 20 to 50 parts by mass of silica fine particles, 5 to 15 parts by mass of a silane coupling agent, and 0.1 to 1.5 parts by mass of a metal chelate compound relative to 100 parts by mass of a polymerizable acrylate compound consisting of 80 to 90% by mass of a hexafunctional or higher-functional urethane (meth)acrylate compound and 20 to 10% by mass of a (meth)acrylate compound (total 100% by mass).

[0060] [Hexafunctional or higher urethane (meth) acrylate compound; hereinafter also referred to as hexafunctional urethane (meth) acrylate]

[0061] Hexafunctional urethane (meth) acrylate is a polymerizable acrylate compound obtained by an addition reaction of a terminal isocyanate compound obtained by reacting a polyol compound with a diisocyanate compound and a (meth) acrylate compound having a plurality of hydroxyl groups, and can be obtained by reacting these two raw materials in a ratio such that the amount of (meth) acryloyl groups is 6 times or more by mole by using a method known per se. For example, hexafunctional urethane (meth) acrylate having three (meth) acryloyl groups at each end of the molecular chain can be obtained by reacting pentaerythritol tri(meth) acrylate with a both-terminal isocyanate (e.g., trihexadiethylenediisocyanate).

[0062] Specific examples of the hexafunctional urethane (meth)acrylate may include dipentaerythritol hexa(meth)acrylate, phenyl glycidyl ether (meth)acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate isophorone diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate toluene diisocyanate urethane prepolymer, glycerol di(meth)acrylate toluene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate hexamethylene diisocyanate urethane oligomer, glycerol di(meth)acrylate isophorone diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate toluene diisocyanate urethane oligomer, and pentaerythritol tri(meth)acrylate isophorone diisocyanate urethane preoligomer, etc., but these may be used alone or in combination of two or more.

[0063] These hexafunctional urethane (meth)acrylates are commercially available, such as, for example, Art Resin series (Negami Chemical Industrial Co., Ltd.), U / UA Oligo series (Shin-Nakamura Chemical Co., Ltd.), Shiko UV series (Nippon Synthetic Chemical Industry Co., Ltd.), and Urethane Acrylate UA series (Kyoeisha Chemical Co., Ltd.), and are generally available.

[0064] When the blending ratio of hexafunctional carbamate (meth) acrylate in the polymerizable acrylate compound is less than 70 mass %, abrasion resistance tends to deteriorate, which is not preferred. When the blending ratio exceeds 90 mass %, cracks tend to occur easily. Considering the hardness and impact resistance of the cured body, the adhesion to the anti-glare layer, and even the coating property, it is preferably used in combination with other polymerizable acrylate compounds listed below.

[0065] [Other polymerizable acrylate compounds]

[0066] Other polymerizable acrylate compounds include (meth)acrylate compounds exemplified by monofunctional (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, lauryl (meth)acrylate, and hydroxyethyl (meth)acrylate; difunctional (meth)acrylate compounds such as ethylene glycol di(meth)acrylate and triethylene glycol di(meth)acrylate; and trifunctional to tetrafunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and trimethylolpropane tri(meth)acrylate.

[0067] Furthermore, examples thereof may include bifunctional to tetrafunctional urethane (meth)acrylate compounds obtained by a polyaddition reaction of a diisocyanate compound and a (meth)acrylate compound having a plurality of hydroxyl groups and in which the number of (meth)acryloyl groups is controlled to be 2 to 4.

[0068] These other polymerizable acrylate compounds are commercially available and thus generally available, and may be used alone or in combination of two or more depending on the purpose.

[0069] [Silicon dioxide fine particles]

[0070] The fine silica particles used for the hard coating are particles that contribute to improving adhesion and coating properties, and there is no particular restriction on their properties. Typically, fine silica particles having a spherical shape, an average particle diameter (D50) of 5nm to 50nm and a refractive index of 1.44 to 1.50 are used. When the average particle diameter (D50) is outside this range, coating properties tend to deteriorate. The average particle diameter of the particles used in the present invention refers to the particle diameter (D50) when the cumulative value is 50% in the particle size distribution obtained by the laser diffraction / scattering method.

[0071] The above-mentioned silica fine particles are non-hollow particles composed of a single particle and having a dense interior without an internal cavity, and generally have a density of 1.9 g / cm 3 The silica fine particles themselves are well known and commercially available. Commercially available silica fine particles are generally supplied in a state dispersed in a solvent, so the solvent is inevitably mixed into the solution (coating liquid) of the curable composition for forming the hard coat layer and the same operation as other solvents is performed.

[0072] [Silane coupling agent]

[0073] The silane coupling agent itself is hydrolyzed to form a dense silicic acid coating. Any known silane coupling agent can be used without limitation, and specific examples of the silane coupling agent can include γ-(meth)acryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-(N-phenylvinylmethyl-β-aminoethylamino)propyltrimethoxysilane hydrochloride, and γ-mercaptopropyltrimethoxysilane, etc.

[0074] Depending on the type, for the purpose of improving solubility in water or solvents, the silane coupling agent can be appropriately converted into a decomposition product by hydrolyzing with a dilute acid or the like in advance, and a hydrolyzate is also included. There is no particular limitation on the method of performing the hydrolysis in advance, and a method of partially hydrolyzing the silane coupling agent using an acid catalyst such as acetic acid is generally used.

[0075] [Metal chelate compounds]

[0076] The metal chelate compound plays a role in introducing a cross-linking structure into the hard coating layer to make it denser.

[0077] As mentioned above, a large amount of hexafunctional urethane (meth) acrylates are used for the hard coat layer of the present invention, so the hard coat layer has excellent flexibility but has reduced compactness. Metal chelate compounds are used to make up for the reduction of such compactness without damaging flexibility. In addition, since such metal chelate compounds are also included in the anti-glare layer, the adhesion between the hard coat layer and the anti-glare layer is further improved.

[0078] The metal chelate compound is a compound in which a chelating agent which is generally a bidentate ligand is coordinated with a metal such as titanium, zirconium and aluminum, and any known compound can be used without limitation.

[0079] Aluminum chelate compounds are preferred, and specific examples thereof include diethoxymono(acetylacetonate)aluminum, monoethoxybis(acetylacetonate)aluminum, diisopropoxymono(acetylacetonate)aluminum, monoethoxybis(ethyl acetoacetate)aluminum, diethoxymono(ethyl acetoacetate)aluminum, and triacetylacetonate aluminum and the like.

[0080] [Formation of hard coat layer]

[0081] The above essential components and any optional components are usually mixed and stirred with the following organic solvents in any order at around room temperature to form a solution (coating solution) of the curable composition. After the solution is applied to a transparent resin substrate, the transparent resin substrate is dried at 50° C. or above to remove the solvent, and then cured by ultraviolet irradiation to form a hard coating layer.

[0082] As optional components, a polymerization initiator for curing the curable composition, a hydrolysis catalyst for promoting condensation curing, an ultraviolet absorber, an organic solvent for dilution to form a coating liquid, and the like are used.

[0083] As the polymerization initiator, a known thermal polymerization initiator or photopolymerization initiator is used in a catalytic amount. As the hydrolysis catalyst, an aqueous solution of an acid such as hydrochloric acid, sulfuric acid, nitric acid or acetic acid is used in a catalytic amount.

[0084] From the viewpoint of coating properties, an organic solvent is generally used so that the total concentration of the essential components and the optional components is 15% to 40% by mass. Suitable organic solvents to be used include alcohol solvents such as ethanol and (iso)propanol; aromatic solvents such as toluene and xylene; acetate solvents such as (iso)butyl acetate; and ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone. When the hard coating is formed, these organic solvents are evaporated and removed.

[0085] There is no particular limitation on the method of applying the coating liquid to the transparent resin substrate, and methods such as dip coating, roll coating, die coating, flow coating and spray coating can be used, but dip coating is preferred from the viewpoint of appearance quality and layer thickness control.

[0086] [Anti-glare layer]

[0087] An anti-glare layer is provided on the hard coating layer. In the present invention, the anti-glare layer is formed by a coating method and is characterized in that it is made of a cured product of a composition containing 0.1 to 15.0 parts by mass of inorganic particles having an average particle size (D50) of 500 nm to 700 nm relative to 100 parts by mass of a polymerizable acrylate compound.

[0088] The thickness of the anti-glare layer is generally 100nm to 500nm. When the thickness is less than 100nm, the inorganic particles tend to be overly prominent. When an anti-reflection film is stacked on the anti-glare layer, the overly prominent inorganic particles will enter the anti-reflection film and increase the refractive index. As a result, the reflectivity increases and damages the anti-reflection property. When the thickness exceeds 500nm, the number of inorganic particles embedded in the binder component increases, and the anti-glare property cannot be fully demonstrated. In addition, the transparency of the anti-glare anti-reflection plate is reduced, which is not preferred. The thickness is preferably 150nm to 450nm, and particularly preferably 200nm to 400nm.

[0089] A preferred formulation of the curable composition is 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 parts by mass of a metal chelate compound, and 0.0 to 45.0 parts by mass of silica fine particles relative to 100 parts by mass of a polymerizable acrylate compound composed of 70 to 90% by mass of a hexafunctional urethane (meth)acrylate and 30 to 10% by mass of a difunctional to tetrafunctional (meth)acrylate compound (100% by mass in total).

[0090] Even when an antireflection film, a protective layer or an antifouling layer is provided on the antiglare layer, the surface characteristics of the formed antiglare layer follow and are maintained. As a result, the antiglare antireflection plate exhibits the above-mentioned surface characteristics (line roughness characteristics) and exhibits antiglare properties.

[0091] [Polymerizable acrylate compound]

[0092] The polymerizable acrylate compound is a general term for acrylate-based polymerizable compounds including the above-mentioned hexafunctional urethane (meth)acrylate and other polymerizable acrylate compounds.

[0093] From the viewpoint of adhesion between the hard coat layer and the anti-reflection layer, the polymerizable acrylate compound in the curable composition for forming the anti-glare layer preferably has a mixed composition of 70% to 90% by mass of hexafunctional urethane (meth)acrylate and 30% to 10% by mass of difunctional to tetrafunctional (meth)acrylate compounds.

[0094] [Inorganic particles]

[0095] In order for the antiglare antireflection sheet of the present invention to express the above-mentioned line roughness characteristics, it is necessary to use inorganic particles having an average particle diameter (D50) of 500 nm to 700 nm.

[0096] When inorganic particles having an average particle size (D50) within the above range are used, the anti-glare anti-reflection plate of the present invention exhibits the above surface characteristics (line roughness characteristics) due to the size, thereby exhibiting anti-glare properties. When the average particle size is less than 500 nm, anti-glare properties cannot be exhibited, and when the average particle size exceeds 700 nm, white blur (white turbidity) occurs, resulting in poor appearance.

[0097] The surface characteristics depend on the average particle size (D50) of the particles used. Therefore, in the case of particles having an average particle size (D50) within the above range, there is no particular limitation on the chemical composition or characteristics of the particles, as long as they do not chemically degrade the anti-glare layer or anti-reflection film. Specific examples of the particles include inorganic oxide particles such as silicon dioxide, aluminum oxide, zirconium oxide, titanium dioxide, and zinc oxide; nitride particles such as aluminum nitride and boron nitride; and inorganic salt particles such as magnesium sulfate and calcium carbonate.

[0098] The inorganic particles need to be blended in an amount of 0.1 to 15.0 parts by mass relative to 100 parts by mass of the polymerizable acrylate compound. If the amount is less than 0.1 parts by mass, the above-mentioned surface characteristics (line roughness characteristics) cannot be exhibited. If the amount is greater than 15.0 parts by mass, white blurring occurs, which is not preferred.

[0099] [Silicon dioxide particles]

[0100] Among inorganic particles, silica particles are particularly suitable in terms of not causing chemical degradation of the anti-glare layer or anti-reflection film and being easily available. Silica particles have the same chemical composition and structure as the silica fine particles used for the above-mentioned hard coating, but are significantly different in that their average particle size (D50) is 500nm to 700nm. Silica particles themselves are known and are usually commercially available in a state dispersed in a solvent. In addition, for the purpose of improving coating properties, the above-mentioned silica fine particles can be compounded.

[0101] [Formation of anti-glare layer]

[0102] The above-mentioned essential components and any optional components are usually mixed and stirred with the following organic solvents in any order at room temperature to form a solution (coating solution) of the curable composition. After the solution is applied to the hard coating layer, the hard coating layer is dried at 50°C or above to remove the solvent, and then cured by irradiating ultraviolet rays to form an anti-glare layer.

[0103] As optional components, there are used metal chelate compounds, polymerization initiators, silica particles, etc. These optional components, organic solvents for dilution, coating methods, etc. are the same as those used for the hard coat layer.

[0104] [Anti-reflective film]

[0105] The anti-glare anti-reflection plate of the present invention is formed by laminating an anti-reflection film on an anti-glare layer. The anti-reflection film includes a low refractive index layer with a refractive index of 1.20 to 1.45 as an essential layer. When the refractive index of the low refractive index layer is outside this range, it cannot function as an anti-reflection film.

[0106] In order to achieve a high degree of anti-reflection, the anti-reflection film is preferably constituted as a two-layer structure including a low refractive index layer with a refractive index of 1.20 to 1.45 and a high refractive index layer with a refractive index of 1.60 to 2.00. It is further preferred that the anti-reflection film is constituted as a three-layer structure having a medium refractive index layer with a refractive index of 1.50 to 1.75 and lower than the high refractive index layer below the high refractive index layer (anti-glare layer side). When the anti-reflection film is composed of a plurality of refractive index layers, the low refractive index layer is located at the outermost layer (viewing side) of the anti-reflection film.

[0107] [Low refractive index layer]

[0108] The low refractive index layer is generally formed by curing a curable composition containing a silane coupling agent, a metal chelate compound, and hollow silica fine particles.

[0109] The hollow silica fine particles are compounded in an amount of 30 to 200 parts by mass relative to 100 parts by mass of the silane coupling agent. In the case of less than 30 parts by mass, a low refractive index cannot be achieved, and in the case of exceeding 200 parts by mass, abrasion resistance decreases.

[0110] In addition to the above-mentioned essential components, the curable composition for forming a low refractive index layer may be compounded with an appropriate amount of an aqueous acid solution such as an aqueous hydrochloric acid solution to promote hydrolysis and condensation of the silane coupling agent.

[0111] [Hollow silica fine particles]

[0112] The hollow silica fine particles contained in the low refractive index layer are particles that control the refractive index of the layer.The average particle diameter (D50) is usually 10 nm to 150 nm, preferably 50 nm to 100 nm, and more preferably 50 nm to 70 nm.

[0113] The hollow silica fine particles have a cavity inside, a porosity of 20% to 70%, preferably 30% to 50%, and generally a refractive index of 1.30 or less.

[0114] Hollow silica fine particles are commercially available in a state of being dispersed in a solvent, and thus they can be appropriately selected, obtained, and used.

[0115] [Formation of low refractive index layer]

[0116] The low refractive index layer is formed in the same manner as the formation of the hard coat layer, and a curable composition solution (coating solution) for forming the low refractive index layer is applied to the anti-glare layer and then dried, and then heated and cured at 70° C. to 120° C. From the viewpoint of antireflection properties, the thickness of the layer is usually set within the range of 50 nm to 200 nm.

[0117] When the anti-reflection film is composed of two layers (i.e., a high refractive index layer and a low refractive index layer), the high refractive index layer is first formed on the anti-glare layer, and then the low refractive index layer is formed on the high refractive index layer. When the anti-reflection layer is composed of three layers (i.e., a medium refractive index layer, a high refractive index layer and a low refractive index layer), the medium refractive index layer is first formed on the anti-glare layer, and then the high refractive index layer is formed on the medium refractive index layer, and then the low refractive index layer is formed on the high refractive index layer.

[0118] The silane coupling agent, metal chelate compound, acid aqueous solution and organic solvent to be used for the coating liquid are the same as those described in the hard coat section. The coating method is also the same as that for the hard coat.

[0119] [Medium refractive index layer / high refractive index layer]

[0120] In order to further improve the antireflection property of the antiglare antireflection sheet of the present invention, it is preferable to construct an antireflection film having a high-order structure including a high-refractive index layer and a medium-refractive index layer.

[0121] The medium refractive index layer preferably has a refractive index of 1.50 to 1.75 and a thickness of 50 to 200 nm. The high refractive index layer preferably has a refractive index of 1.60 to 2.00 and a thickness of 50 to 200 nm. The refractive index of the high refractive index layer in the antireflection film must be higher than that of the medium refractive index layer.

[0122] The high refractive index layer and the medium refractive index layer are usually formed by curing a curable composition containing 100 to 500 parts by mass of metal oxide particles per 100 parts by mass of a silane coupling agent. The amount of the metal oxide particles is appropriately determined depending on the metal oxide to be used and the refractive index to be set.

[0123] Similar to the low refractive index layer, the curable composition for forming the high refractive index layer and the medium refractive index layer may be compounded with an appropriate amount of an aqueous acid solution.

[0124] [Metal oxide particles]

[0125] For the purpose of setting the refractive index of the medium refractive index layer and the high refractive index layer to fall within the above-described predetermined range, metal oxide particles are used.

[0126] Typically, the metal oxide particles have an average particle size of 10 nm to 100 nm and a refractive index of 1.70 or more and 2.80 or less. Specific examples of the metal oxide particles to be used include zirconium oxide particles (refractive index = 2.40); composite zirconium metal oxide particles in which zirconium oxide and other oxides such as silicon oxide are combined at the molecular level to adjust the refractive index; titanium oxide particles (refractive index = 2.71); and composite titanium metal oxide particles in which titanium oxide and other oxides such as silicon oxide and zirconium oxide are combined at the molecular level to adjust the refractive index, etc. These metal oxide particles are selected or appropriately combined to adjust the refractive index of the layer to the desired refractive index. Such particles themselves are known and are commercially available in a state dispersed in a solvent.

[0127] [Organic-inorganic composite compounds]

[0128] For the purpose of improving the adhesion between the anti-glare layer and the low refractive index layer, an organic-inorganic composite compound may be compounded into the medium refractive index layer and the high refractive index layer.

[0129] The organic-inorganic composite compound is, for example, a composite compound to which an alkoxysilyl group is bonded, which is obtained by reacting a hydrolyzable alkoxysilane compound with a bisphenol A type epoxy resin having an epoxy equivalent of 180 to 5000. When the composite compound is cured, crosslinking of the terminal epoxy group and higher-order siloxane crosslinking (silicon dioxide formation) caused by a sol-gel reaction of the alkoxysilyl group occur, resulting in a cured product that does not have Tg like glass and has the advantages of both organic and inorganic materials.

[0130] There are various types of organic-inorganic composite compounds. For example, there are composite compounds having a structure in which an alkoxysilyl group is bonded to a polymer such as a bisphenol A type epoxy resin (hereinafter also referred to as a silane-modified epoxy compound), a novolac type phenolic resin, or a polyamic acid compound.

[0131] In the present invention, a silane-modified epoxy compound is preferably used as the organic-inorganic composite compound because it has excellent adhesion between the antiglare layer and the refractive index layer and is easily available.

[0132] [Formation of Medium Refractive Index Layer and High Refractive Index Layer]

[0133] The medium refractive index layer and the high refractive index layer are formed in the same manner as the low refractive index layer, and are formed by applying each composition solution (coating liquid) onto the antiglare layer in the above order, drying it, and then heating and curing it at 70°C to 120°C.

[0134] The silane coupling agent, metal chelate compound, acid aqueous solution and organic solvent to be used for each curable composition solution are the same as those described in the section of the hard coat layer. The coating method is also the same as that for the hard coat layer.

[0135] [Protective layer]

[0136] In the present invention, a suitable protective layer is composed of a cured product obtained by curing a curable composition containing 7.5 to 35 parts by mass of spherical silica fine particles having an average particle diameter of 10 nm or less relative to a total of 100 parts by mass of 90 to 98 parts by mass of a silane coupling agent and 10 to 2 parts by mass of a metal chelate compound. In addition, it is preferred that the refractive index of the cured product after curing is 1.45 to 1.50, and the thickness of the layer is 10 nm to 15 nm.

[0137] The silane coupling agent, metal chelate compound and silica fine particles to be compounded in the curable composition are the same as those used to form the hard coat layer and can be used without any limitation. This also applies to the coating method and the organic solvent used to form the coating solution.

[0138] [Antifouling layer]

[0139] The antifouling layer is a layer provided to express a high degree of antifouling property, generally having a thickness set within a range of 5 nm to 15 nm, and is made of a polymer of a fluorine-containing silicon compound.

[0140] Specifically, the polymer of the fluorine-containing silicon compound is a polymer obtained by polycondensation of a compound having a perfluoropolyether structure as a main chain as a main component and having an alkoxysilyl group as a hydrolyzable group at one or both ends of the main chain. The presence of the perfluoropolyether structure reduces the adhesion of grease, resulting in high antifouling properties.

[0141] The fluorine-containing silicon compound is commercially available as a solution dissolved in an organic solvent such as isopropyl ether, hexane or a fluorine-based organic solvent, as products such as "Novec (registered trademark)" manufactured by 3M Company, "DowCorning (registered trademark)" manufactured by Toray Dow Corning, "SHIN-ETSU SUBELYN (registered trademark)" manufactured by Shin-Etsu Chemical, "Opttool" manufactured by Daikin, and "SURECO (registered trademark)" manufactured by Asahi Glass, so it is preferable to obtain and use these.

[0142] A solution (coating liquid) containing a fluorine-containing silicon compound is applied onto the protective layer by a conventional method and then maintained at a temperature of about 100° C. for about 6 to 8 hours to dry and cure into a polymer, thereby forming an antifouling layer.

[0143] [Example]

[0144] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, all feature combinations described in the embodiments are not necessarily essential to the technical solutions of the present invention.

[0145] Various components and abbreviations and measuring methods used in the following Examples and Comparative Examples are as follows.

[0146] [Polymerizable acrylate compound]

[0147] [Hexafunctional urethane (meth)acrylate]

[0148] ac-6: Pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer

[0149] [Bifunctional (meth)acrylate compound]

[0150] ac-2: triethylene glycol diacrylate

[0151] [Trifunctional (meth)acrylate compound]

[0152] ac-3: polyester urethane acrylate

[0153] ac-4: Pentaerythritol triacrylate

[0154] [Silicon dioxide fine particles]

[0155] sp-1: solid sphere, average particle size (D50) = 7 nm, refractive index = 1.46, IPA dispersion, solid content: 20 wt%

[0156] sp-2: solid sphere, average particle size (D50) = 40 nm, refractive index = 1.46, MEK dispersion, solid content: 30 wt%

[0157] sp-3: hollow particles, average particle size (D50) = 60 nm, refractive index = 1.30, IPA dispersion, solid content: 20 wt%

[0158] [Silicon dioxide particles]

[0159] sp-4: solid sphere, average particle size (D50) = 500nm, refractive index = 1.46, MEK dispersion, solid content: 67wt%

[0160] sp-5: solid sphere, average particle size (D50) = 700nm, refractive index = 1.46, MeOH dispersion, solid content: 50wt%

[0161] sp-6: solid sphere, average particle size (D50) = 300 nm, refractive index = 1.46, MeOH dispersion, solid content: 33 wt%

[0162] sp-7: solid sphere, average particle size (D50) = 900 nm, refractive index = 1.46, MEK dispersion, solid content: 67 wt%

[0163] [Silane coupling agent]

[0164] γ-GPS: γ-glycidoxypropyltrimethoxysilane

[0165] [Metal chelate compounds]

[0166] ATAA: Aluminum tris(acetylacetonate)

[0167] [Metal oxide particles]

[0168] z-1: zirconium oxide particles, average particle size = 60 nm, refractive index = 2.42, PGM (1-methoxy-2-propanol) dispersion, solid content: 53 wt%

[0169] z-2: zirconium oxide particles, average particle size = 30 nm, refractive index = 2.40, BuOH / EtOH dispersion, solid content: 15 wt%

[0170] [Organic-inorganic composite compounds]

[0171] sep: silane-modified epoxy compound, DMDG (diethylene glycol dimethyl ether) dispersion

[0172] [Photopolymerization initiator]

[0173] pi-1: 1-Hydroxy-cyclohexyl-phenyl ketone

[0174] pi-2: 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one

[0175] [Ultraviolet light absorber]

[0176] UV: Benzotriazole ultraviolet absorber

[0177] [Hydrolysis catalyst]

[0178] HCl: 0.05N hydrochloric acid solution

[0179] [Organic solvents]

[0180] IPA: Isopropyl alcohol

[0181] MIBK: Methyl isobutyl ketone

[0182] SBAC: sec-butyl acetate

[0183] NPA: n-propanol

[0184] Eta Cohol: A mixture of ethanol and isopropyl alcohol

[0185] [Visual average reflectivity]

[0186] The reflectivity at the lowest point (surface of the anti-glare anti-reflection plate) was measured at a scanning speed of 1000 nm / min in a wavelength range of 380 nm to 780 nm using a UV-visible spectrophotometer "V-650" manufactured by Jasco International Co., Ltd. The visual average reflectivity was calculated by multiplying the obtained reflectivity by the weight coefficient specified in JIS-Z-8722. It shows that the smaller the value, the better the anti-reflectivity.

[0187] [Average visual transmittance]

[0188] The transmittance at the peak top was measured in the range of 380 nm to 780 nm at a scanning speed of 1000 nm / min using an ultraviolet visible spectrophotometer “V-650” manufactured by Jasco International Co., Ltd., and the visual average transmittance was calculated by multiplying the obtained transmittance by the weighting coefficient specified in JIS-Z-8722.

[0189] [Various line roughness characteristics]

[0190] Based on the Japanese Industrial Standard "JIS B 0601", various line roughness characteristics were measured by using a laser microscope "VK-X1000" manufactured by KEYENCE CORPORATION. The values ​​of the line roughness characteristics were automatically calculated using analysis software built into the measuring device. The measurement distance was 276 μm, and the first and last total of 26 μm were cut off.

[0191] [Maximum peak height (Rp) / Maximum valley depth (Rv)]

[0192] This is a characteristic value uniquely set in the present invention, and is a value obtained by dividing the maximum peak height (Rp) obtained by using a laser microscope "VK-X1000" manufactured by KEYENCE CORPORATION by the maximum valley depth (Rv).

[0193] [Haze value]

[0194] The haze value is measured by using a haze meter "HM-150N" manufactured by Murakami Color Research Laboratory based on Japanese Industrial Standard "JIS K 7136". When the haze value is less than 0.5%, glare is observed on the surface, and when the haze value exceeds 20.0%, white turbidity occurs, preventing the plate from functioning as an anti-glare anti-reflection plate.

[0195] [Refractive index]

[0196] The coating liquid for each refractive index layer was coated on an acrylic resin substrate to a thickness of 100 nm and cured to form each refractive index layer. Next, the refractive index of each layer was calculated from the bottom value of the reflection spectrum by using a spectrophotometer "V-650" manufactured by Jasco International Co., Ltd.

[0197] [Example 1]

[0198] A hard coating layer, an antiglare layer and an antireflection film were sequentially formed on a transparent resin substrate made of polymethyl methacrylate resin (PMMA) with a thickness of 1 mm (80 mm long×50 mm wide) by using the following method. The thickness of each layer was adjusted by the pull-up speed from the dip coating solution.

[0199] [Hard coat layer forming coating liquid; HC-1]

[0200] Polymerizable acrylate compound: The blending ratio relative to 100 parts by mass of the total amount of the compound is shown in parentheses (the same applies hereinafter).

[0201] -ac-6: 126.7 g (85.1 parts by mass)

[0202] -ac-2: 8.0 g (5.4 parts by mass)

[0203] -ac-3: 14.1 g (9.5 parts by mass)

[0204] Silica fine particles

[0205] -sp-1: 40.0 g (26.9 parts by mass), dispersion medium IPA 160.0 g

[0206] Silane coupling agent

[0207] -γ-GPS: 12.2 g (8.2 parts by mass)

[0208] Metal chelate compounds

[0209] -ATAA: 1.0 g (0.7 parts by mass)

[0210] UV absorber

[0211] -UV; 11.2g

[0212] Photopolymerization initiator

[0213] -pi-1; 6.4g

[0214] -pi-2; 1.6g

[0215] Hydrolysis catalyst

[0216] -HCl; 2.8g

[0217] Organic solvents

[0218] -IPA; 308.0g

[0219] -MIBK; 308.0g

[0220] [Anti-glare layer forming coating liquid; AG-1]

[0221] Polymerizable acrylate compounds:

[0222] -ac-6; 25.2 g (70.0 parts by mass)

[0223] -ac-4; 10.8 g (30.0 parts by mass)

[0224] Silica fine particles

[0225] -sp-2; 4.0 g (11.1 parts by mass), dispersion medium MEK 9.3 g

[0226] Silica particles

[0227] -sp-4; 0.2g (0.6 parts by mass), dispersion medium MEK 0.1g

[0228] Metal chelate compounds

[0229] -ATAA: 0.2 g (0.6 parts by mass)

[0230] Photopolymerization initiator

[0231] -pi-2; 1.4 g (3.9 parts by mass)

[0232] Organic solvents

[0233] -IPA; 565.0g

[0234] -MIBK; 383.8g

[0235] Coating liquid for forming low refractive index layer; l-1: The compounding ratio relative to 100 parts by mass of the silane coupling agent is shown in parentheses.

[0236] Silane coupling agent

[0237] -γ-GPS; 3.6 g (100 parts by mass)

[0238] Silica fine particles

[0239] -sp-3; 1.7 g (46.2 parts by mass), dispersion medium IPA 6.7 g

[0240] Metal chelate compounds

[0241] -ATAA; 0.1 g (2.8 parts by mass)

[0242] Hydrolysis catalyst

[0243] -HCl; 1.7g

[0244] Organic solvents

[0245] -IPA; 147.7g

[0246] -NPA; 49.2g

[0247] -SBAC; 49.2g

[0248] First, the transparent resin substrate is dip-coated with a coating solution for forming a hard coating layer having the above composition, dried at 60°C for 5 minutes, and then irradiated with ultraviolet rays from a mercury lamp for 1 minute for UV curing, thereby forming a hard coating layer with a thickness of 2 μm. Next, the substrate with the hard coating layer is dip-coated with a coating solution for forming an anti-glare layer, dried at 60°C for 8 minutes, and then irradiated with ultraviolet rays from a mercury lamp for 1 minute for UV curing, thereby forming an anti-glare layer with a thickness of 200 nm. Thereafter, the substrate with the hard coating layer and the anti-glare layer is dip-coated with a coating solution for forming a low refractive index layer, and then heat-treated at 90°C for 20 minutes to form an anti-reflection film (low refractive index layer) with a thickness of 95 nm and a refractive index of 1.34, thereby obtaining the anti-glare anti-reflection plate of the present invention.

[0249] Various physical properties and characteristics of the obtained antiglare antireflection plate were measured and evaluated according to the above-mentioned measuring methods. Table 2 shows the layer thickness and optical characteristics of each layer, and Table 3 shows the surface characteristics (various line roughness characteristics).

[0250] Figure 1 shows the laser photograph of the plate surface obtained, and Figure 2 The measured cross-section curve and the roughness curve are shown. From both figures it can be seen that there are large convex parts.

[0251] [Examples 2 and 3]

[0252] An antiglare antireflection plate was produced in the same manner as in Example 1 except that the antiglare layer-forming coating liquid was changed to a coating liquid having a composition shown in Table 1, and various physical properties and characteristics were measured.

[0253]

[0254] [Example 4]

[0255] Except that the antireflection film is constituted to have a three-layer structure including a medium refractive index layer, a high refractive index layer and a low refractive index layer, an antiglare antireflection plate is produced in the same manner as in Example 1, and various physical properties and characteristics are measured. The results are shown in Tables 2 and 3.

[0256] Regarding the antireflection film, first, a transparent resin substrate having a hard coating layer and an antiglare layer formed thereon in sequence was dip-coated with the following coating solution for forming a medium refractive index layer, and then heated at 90°C for 20 minutes to form a medium refractive index layer (layer thickness of 85nm, refractive index of 1.64), the medium refractive index layer was dip-coated with the following coating solution for forming a high refractive index layer, and then heated at 90°C for 20 minutes to form a high refractive index layer (layer thickness of 80nm, refractive index of 1.77), and then a low refractive index layer was formed in the same manner as in Example 1, thereby forming an antireflection film having a three-layer structure (film thickness of 255nm).

[0257] [Coating liquid for forming a medium refractive index layer; m-1]: The compounding ratio relative to 100 parts by mass of the silane coupling agent is shown in parentheses.

[0258] Silane coupling agent

[0259] -γ-GPS; 1.5 g (100 parts by mass)

[0260] Organic-inorganic composite compounds

[0261] -sep; 2.4g (160 parts by mass), dispersion medium DMDG 2.4g

[0262] Metal oxide particles

[0263] -z-1; 4.8 g (320 parts by mass), dispersion medium PGM 4.3 g

[0264] Metal chelate compounds

[0265] -ATAA; 0.1 g (6.7 parts by mass)

[0266] Hydrolysis catalyst

[0267] -HCl; 0.9g

[0268] Organic solvents

[0269] -IPA; 97.4g

[0270] -SBAC; 146.2g

[0271] Coating liquid for forming high refractive index layer; h-1: The compounding ratio relative to 100 parts by mass of the silane coupling agent is shown in parentheses.

[0272] Silane coupling agent

[0273] -γ-GPS; 1.3 g (100 parts by mass)

[0274] Metal oxide particles

[0275] -z-2; 4.5 g (346 parts by mass), dispersion medium BuOH / EtOH 30.0 g

[0276] Metal chelate compounds

[0277] -ATAA: 0.2 g (15.4 parts by mass)

[0278] Hydrolysis catalyst

[0279] -HCl; 0.3g

[0280] Organic solvents

[0281] -SBAC; 11.2g

[0282] -Eta Cohol; 212.5g

[0283] [Examples 5 to 7]

[0284] An antiglare antireflection plate was produced in the same manner as in Example 4 except that the antiglare layer-forming coating liquid was changed to a coating liquid having a composition shown in Table 1, and various physical properties and characteristics were measured.

[0285]

[0286] [Table 3]

[0287] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Ra[μm] 0.04 0.08 0.20 0.05 0.11 0.05 0.07 RSm[μm] 47.21 39.83 24.25 68.39 41.87 30.61 32.34 R 0.82 1.11 0.69 0.66 0.88 -0.01 0.91 R 3.26 4.44 3.39 3.32 3.48 2.91 3.67 Rp[μm] 0.20 0.45 0.86 0.24 0.48 0.18 0.31 Rv[μm] 0.07 0.21 0.65 0.14 0.24 0.15 0.15 Rp / Rv 2.86 2.14 1.32 1.71 2.00 1.20 2.10

[0288] Note: Measurement distance: 276μm, cutoff: 26μm

[0289] [Comparative Examples 1 to 6]

[0290] An antiglare antireflection sheet was produced in the same manner as in Examples 1 and 4 except that the antiglare layer-forming coating liquid was changed to a coating liquid having a composition shown in Table 4, and various physical properties and characteristics were measured.

[0291]

[0292]

[0293] [Table 6]

[0294]

[0295] Note: Measurement distance: 276μm, cutoff: 26μm

[0296] Comparative Example 1 is an example that does not contain inorganic particles having a large average particle diameter. In Comparative Example 1, the haze value is small and surface glare is clearly observed. Figure 3 A laser photograph of the surface of the plate obtained in this Comparative Example 1 is shown, and Figure 4 The measured cross-section curve and the roughness curve are shown. From both figures it can be seen that there are no large convex parts.

[0297] Comparative Example 2 is an example containing a large amount of inorganic particles having a large average particle size. In Comparative Example 2, the haze value is large and white turbidity occurs, so the antiglare antireflection plate has no product value. Therefore, the line roughness property was not measured.

[0298] Comparative Example 3 shows a case where the average particle size of the inorganic particles is too small. In Comparative Example 3, the haze value is small and surface glare is clearly observed.

[0299] Comparative Example 4 is an example in which the average particle size of the inorganic particles is too large. In Comparative Example 4, the haze value is large and white turbidity occurs, so the antiglare antireflection sheet has no product value. Therefore, the line roughness property was not measured.

[0300] Comparative Example 5 is an example in which the antireflection film has a three-layer structure and does not contain inorganic particles having a large average particle diameter. In Comparative Example 5, the haze value is small and surface glare is clearly observed.

[0301] Comparative Example 6 is an example in which the anti-reflection film has a three-layer structure and contains a large amount of inorganic particles having a large average particle size. In Comparative Example 6, the haze value is large and white turbidity occurs, so the anti-glare anti-reflection plate has no product value. Therefore, the line roughness property was not measured.

Claims

1. An anti-glare anti-reflection plate, comprising: Hard coating; Anti-glare layer; and Anti-reflective film, The hard coating layer, the anti-glare layer and the anti-reflection film are sequentially laminated on a transparent resin substrate. The anti-glare layer is made of a cured product of a composition, wherein the composition contains 0.1 to 15.0 parts by mass of inorganic particles having an average particle size (D50) of 500 nm to 700 nm relative to 100 parts by mass of a polymerizable acrylate compound, and The line roughness characteristics defined in JIS B 0601 on the surface of the antiglare antireflection sheet are as follows: The arithmetic mean roughness (Ra) is 0.03 μm or more and 0.20 μm or less, The average length (RSm) is 10 μm or more and 70 μm or less, The skewness (Rsk) is greater than -0.05 and less than 1.50, The kurtosis (Rku) is 2.0 or more and 5.0 or less, and The maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less.

2. The anti-glare anti-reflection sheet according to claim 1, wherein the anti-reflection film is composed of a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 nm to 200 nm, the inorganic particles are silica particles, and the anti-glare anti-reflection sheet has a haze value of 0.5% to 20.0%.

3. The anti-glare anti-reflection sheet according to claim 1, wherein The anti-reflection film includes, in sequence, a medium refractive index layer with a refractive index of 1.50 to 1.75 and a layer thickness of 50 nm to 200 nm, a high refractive index layer with a refractive index of 1.60 to 2.00 and a layer thickness of 50 nm to 200 nm, and a low refractive index layer with a refractive index of 1.20 to 1.45 and a layer thickness of 50 nm to 200 nm, the refractive index of the high refractive index layer is higher than that of the medium refractive index layer, the inorganic particles are silica particles, and the haze value of the anti-glare anti-reflection plate is 0.5% to 15.0%.

4. The anti-glare anti-reflective plate according to claim 1, wherein the anti-glare layer is made of a cured product of a composition, wherein the composition comprises 70% to 90% by mass of a hexafunctional urethane (meth)acrylate compound and 30% to 10% by mass of a difunctional to tetrafunctional (meth)acrylate compound relative to 100 parts by mass of a polymerizable acrylate compound (total 100% by mass), 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 parts by mass of a metal chelate compound and 0.0 to 45.0 parts by mass of silica fine particles.

5. The anti-glare anti-reflection sheet according to claim 1, wherein The antiglare layer has an average layer thickness of 100 nm to 500 nm.

6. The anti-glare anti-reflection sheet according to claim 1, wherein A protective layer and an antifouling layer are further laminated in this order above the antireflection film (on the viewing side).

Citation Information

Patent Citations

  • Antidazzle film and its manufacturing method, antireflection film, polarizing plate and image display device

    JP2004333936A

  • Transparent substrate having antiglare properties and antireflection properties and method for producing the same

    JP2018077279A